Improved Energy Aware Cluster based Data Routing Scheme for WSN - Khalid Haseeb; Kamalrulnizam Abu Bakar; Abdul Hanan Abdullah; Tasneem Darwish; Fasee Ullah; Adnan Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Wireless sensor network (WSN) consists of several tiny devices that are dispersed randomly for gathering network field. Clustering mechanism divides the WSN into different sub-regions called clusters. Individual cluster is consisting of cluster head (CH) and member nodes. The main research challenges behind clustering mechanism are to optimize network overheads with efficient data delivery. Sensor nodes are operated by batteries and practically it is not feasible to replace them during sensing the environment so energy should be effectively utilized among sensors for improving overall network performance. This research paper presents an improved energy aware cluster based data routing (i-ECBR) scheme, by dividing the network regions into uniform sized square partitions and localized CH election mechanism. In addition, consistent end-to-end data routing is performed for improving data dissemination. Simulation results illustrate that our proposed scheme outperforms than existing work in terms of different performance metrics.